QUANTIFYING LINEAR URBAN SPRAWL THROUGH OPEN SPACE FRAGMENTATION INDEX: EVIDENCE FROM THE TOMOHON–SONDER PERI-URBAN CORRIDOR, INDONESIA - Octavianus Hendrik Alexander Rogi; Ingerid Lidia Moniaga; Michael Moldy Rengkung (CV. TOTUS TUUS, 2026)
Urban sprawl is characterized by the horizontal expansion of urban areas, which puts pressure on natural resources, increases land consumption, and increases the need for infrastructure investment and maintenance. One key attribute used to explain this phenomenon is the fragmentation of open space due to uncontrolled urban growth. Therefore, city governments need to monitor trends in urban sprawl to formulate anticipatory strategies to address its consequences. This study explores the use of regression analysis to interpret linear urban sprawl in a peri-urban corridor using a simple open space fragmentation index (the ratio of open space to built-up land) as an indicator. This analysis focuses on the variation of the open space fragmentation index based on the relative distance from the point of origin of urban growth. This case study was conducted in an urban corridor in Tomohon City, North Sulawesi, Indonesia. The results demonstrate that this approach is effective in verifying and interpreting the phenomenon of urban sprawl and has the potential to provide useful feedback for local governments.